Egyptian Association of Vascular Biology and Atherosclerosis Consensus on The Usage of SGLT2 Inhibitors in Heart Failure. (8th October 2021) - Reda, Ashraf; Elserafy, Ahmed Shawky; Farag, Elsayed; Mostafa, Tamer; Farag, Nabil; Elbahary, Atef; Sanad, Osama; Tabl, Mohamed Abdelshafy; Bendary, Ahmed; Elkersh, Ahmed; Ashraf, Mohamed; Attia, Ihab; et al.
Abstract: Aims: Analysis of SGLT2i data from DAPA-HF and EMPEROR- reduced trials to put a simplified consensus statement on the use of these glucose lowering agents in patients with established heart failure. Methods and Results: Sixty experts in the field of cardiology revised the literature of the SGLT2i in heart failure, their recommended indications, and their contraindications. Data from DAPA-HF and EMPEROR-reduced trials were tabulated and statistically analysed. SGLT2 inhibitors investigated initially for their glucose lowering capability, have shown a significant benefit in chronic heart failure eit reduced ejection fraction (HFrEF). Conclusions: We recommend early use of dapagliflozin 10 mg, or empagliflozin 10 mg in patients suffering from symptomatic chronic HFrEF, whether the patient is diabetic or non, to improve heart failure hospitalization, death, symptoms, and decline of renal function.